violence during the final Formativein the Peruvian North Coast - Pezo Lanfranco, Luis (2011)
The processcs involed in increasing social complexity have been studied archacologicallythrough several approaches.One of them is the study of interpersonal violence. Violence has beenassociared with nwe forms of social structure, inter-community competition for scarce resources and new forms of political practice. In the Central Andes, it is likely that tha¿e process of transition from egalitarian to ranked societies would have occurred during the Formative perios(1800-1BC). Using osteological markers, this paper approach's the rypes of violence ande their impact on 30 individuals of the Salinar phase(400-1BC) of the puemape site on the Peruvian north coast.For comparative issues,we analyze two earlier populations at the site (Early Puemape,MNI=26 and Middle Puemape,MNI=29) adn others of the region. Higher frequencies of trauma in males (25%cranial and30% facialinjuries and other types)and some contextual data are consistent wwith intercomunitary violence and conform the archacological interpretations which have srated that the Salinas period was a violent epoch at the pnset of the development of clearly stratified societics